Assessing landscape plans with abbreviated pair-wise comparisons in the AHP (Analitic Hierarchy Process) - Lakićević Milena D.; Reynolds Keith M.; Srđević Bojan M. (Zbornik Matice Srpske za Prirodne Nauke, 2019)
This paper demonstrates the application of the Analytic Hierarchy Process (AHP) in assessing landscape plans using the option of abbreviated pair-wise comparisons to simplify the weight elicitation process for decision makers. Whereas the standard AHP elicitation procedure requires a full set of pairwise comparisons among all criteria at each node of the decision hierarchy in order to derive criterion weights for the decision model, the abbreviated pairwise method uses a minimal spanning set of pairwise comparisons, and remaining comparisons are then derived by transitivity rules. In this paper is presented the abbreviated pairwise method with a case study in which alternative management plans are evaluated for the Zvezdarska forest of Belgrade, Serbia. The analysis was performed with the Criterium DecisionPlus software, which fully implements the AHP methodology, and provides useful diagnostics on AHP decision models. As a conclusion, some of the key advantages and disadvantages of the abbreviated pairwise variant of the AHP method are demonstrated. One of the key qualities of the Criterium DecisionPlus software is a clear and easy graphical representation of the results. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 174003: Theory and application of analytic hierarchy process (AHP) in multi-criteria decision making under conditions of risk and uncertainty (individual and group context)]